A kind of fluorine-free oil-proof paper and its production method

By optimizing the base paper preparation process and multi-layer coating process, environmentally friendly materials are used to improve the oil-proof performance and physical properties of fluorine-free oil-proof paper, solving the environmental and health problems of traditional fluorine-containing oil-proof paper, and achieving high-performance, environmentally friendly fluorine-free oil-proof paper products.

CN119083225BActive Publication Date: 2025-03-18QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411212326.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-03-18
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Due to its bioaccumulative properties and environmental stability, traditional fluorine-containing oil-resistant papers face strict restrictions on their production and use. The existing fluorine-free oil-resistant papers have shortcomings in oil-resistant and physical properties.

Method used

By optimizing the base paper preparation process and multi-layer coating process, chitosan solution, nanocellulose and emulsifier are used as the base coating, and environmentally friendly materials such as hydroxypropyl starch, amylase, and acrylate are combined as the top coating to improve the oil resistance and physical properties of the paper.

Benefits of technology

It has achieved improvements in oil-free oil-proof paper in oil-proof grade, quantification, whiteness, opacity, smoothness and tensile strength, meeting the standards of high-end products in the market and reducing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119083225B_ABST
    Figure CN119083225B_ABST
Patent Text Reader

Abstract

The present invention provides a fluorine-free oil-proof paper and a production method thereof, belonging to the field of oil-proof paper production. The present invention comprises the following steps: base paper preparation, primary bottom layer coating, secondary bottom layer coating, and surface layer coating. The basis weight of the oil-proof paper of the present invention is 60-65 g / m 2 , whiteness 80‑84% ISO, opacity >87%, smoothness 110‑120s, transverse tensile strength 2.0‑2.1kN / m, longitudinal tensile strength 3.9‑4.3kN / m, oil resistance grade ≥9.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of oil-proof paper production and relates to fluorine-free oil-proof paper and a production method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] As an important packaging material, greaseproof paper has been widely used in many industries such as food, medicine, and cosmetics. Especially in the field of food packaging, greaseproof paper is favored for its good greaseproof performance. It can effectively prevent the grease in food from penetrating to the outside of the packaging and maintain the freshness and taste of the food.

[0004] Traditional oil-proof paper mainly achieves oil-proof effect by coating fluorinated compounds on the surface of paper. Such fluorinated compounds, such as perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), are widely used due to their excellent water- and oil-repellent properties. However, these compounds are highly bioaccumulative and environmentally stable, difficult to degrade in the natural environment, and pose a potential threat to ecosystems and human health. Therefore, with the strengthening of global control over persistent organic pollutants (POPs), the production and use of fluorinated oil-proof paper are facing increasingly stringent restrictions.

[0005] In recent years, with the improvement of environmental protection awareness and the introduction of relevant laws and regulations, the research and development of fluorine-free oil-proof paper has received widespread attention. Fluorine-free oil-proof paper not only needs to have good oil-proof performance, but also should meet a series of physical performance index requirements, such as basis weight, bulk, whiteness, opacity, smoothness and tensile strength. At present, there are some fluorine-free oil-proof paper products on the market, but the performance of these products is not the same. Although some products have a high oil-proof grade, they are insufficient in other physical properties, such as low tensile strength or unsatisfactory smoothness. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a fluorine-free oil-proof paper and a production method thereof. By optimizing the base paper preparation process, wet-end chemical formulation and multi-layer coating process, a fluorine-free oil-proof paper that is both environmentally friendly and has excellent oil-proof and physical properties is successfully developed.

[0007] The present invention successfully develops a fluorine-free oil-proof paper that is both environmentally friendly and has excellent oil-proof performance by optimizing the base paper preparation process and coating treatment process. Specifically, the present invention uses chitosan solution, nanocellulose and emulsifier as the main components of the bottom coating solution. These components are not only non-toxic and harmless, degradable, but also can effectively improve the oil-proof performance of paper. At the same time, in the surface coating process, the present invention selects environmentally friendly materials such as hydroxypropyl starch, amylase, acrylate and water, which further enhances the oil-proof effect and physical properties of the oil-proof paper.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] The first aspect of the present invention provides a fluorine-free oil-proof paper, comprising: base paper, a first bottom layer, a second bottom layer, and a surface layer; the base paper is loaded with the first bottom layer, the second bottom layer, and the surface layer in sequence;

[0010] The pulp used in the base paper is composed of coniferous chemical pulp, broadleaf chemical pulp, poplar chemical mechanical pulp, filler, cationic starch, retention aid, brightener, and neutral glue;

[0011] The coating of the first bottom layer is composed of pigment, adhesive, water repellent, rheological agent, thickener, defoamer and bactericide;

[0012] The coating of the second bottom layer is composed of chitosan solution, nanocellulose and emulsifier;

[0013] The coating of the surface layer consists of hydroxypropyl starch, amylase, acrylate and water.

[0014] In some embodiments, the mass ratio of the coniferous chemical pulp, the broadleaf chemical pulp, and the poplar chemical mechanical pulp is 20-30:50-60:20-30;

[0015] In some embodiments, the amount of filler is 190-210 kg / ton of paper;

[0016] In some embodiments, the cationic starch is used in an amount of 10-11 kg / ton of paper;

[0017] In some embodiments, the amount of the brightener is 3-3.5 kg / ton of paper;

[0018] In some embodiments, the retention agent is used in an amount of 0.2-0.3 kg / ton of paper;

[0019] In some embodiments, the amount of the neutral glue used is 10-15 kg / ton of paper.

[0020] It should be noted that the present invention does not specifically limit the pulp raw materials, preparation processes, etc. of coniferous chemical pulp, broadleaf chemical pulp, and poplar chemical mechanical pulp. The above pulps only need to meet the requirements of beating degree and beating concentration to meet the production requirements of base paper and oil-proof paper of the present invention. Therefore, in some embodiments, the coniferous chemical pulp has a beating degree of 43-47°SR and a beating concentration of 3.9-4.2%;

[0021] In some embodiments, the broadleaf chemical pulp has a beating degree of 28-32°SR and a beating concentration of 3.8-4.3%;

[0022] In some embodiments, the poplar chemical mechanical pulp has a beating degree of 35-37°SR and a beating concentration of 3.4-3.6%;

[0023] In some embodiments, the filler is light calcium, nano calcium and diatomaceous earth; the weight ratio of the light calcium, nano calcium and diatomaceous earth is 3-4:1:1, and the filler concentration is 14-16%;

[0024] It should be noted that "filler concentration of 14-16%" means that the filler is prepared into a solution with a concentration of 14-16% and then added to the slurry. The meanings of cationic starch, retention aid, brightener and neutral gum concentration are the same.

[0025] In some embodiments, the concentration of the cationic starch is 2-3%;

[0026] In some embodiments, the retention aid is cationic polyacrylamide or polyethyleneimine or polydimethyldiallylammonium chloride, and the concentration is 2.3-2.7%;

[0027] In some embodiments, the whitening agent is tetrasulfonic acid or hexasulfonic acid;

[0028] In some embodiments, the neutral glue is AKD or cationic rosin glue, the concentration of AKD is 15%, and the concentration of cationic rosin glue is 35%.

[0029] In some embodiments, the mass ratio of the pigment: adhesive: water repellent: rheological agent: thickener: defoamer: bactericide is 100:10-12:0.4-0.6:0.4-0.6:0.4-0.6:0.1-0.2:0.1-0.2.

[0030] In some embodiments, the pigment is light calcium or china clay;

[0031] In some embodiments, the adhesive is carboxylated styrene-butadiene latex or acrylic emulsion;

[0032] In some embodiments, the water repellent is potassium zirconium carbonate, modified glyoxal, polyamide polyurea or ammonium zirconium carbonate;

[0033] In some embodiments, the rheological agent is modified acrylic acid;

[0034] In some embodiments, the thickener is polyurethane emulsion, carboxymethyl cellulose, hydroxyethyl cellulose, polyvinyl alcohol or polyacrylamide;

[0035] In some embodiments, the defoaming agent is polyether, C18-C20 higher fatty alcohol or silicone;

[0036] In some embodiments, the bactericide is an organic bromine;

[0037] In some embodiments, the coating weight of a primary coating is 4-6 g / m 2 .

[0038] In some embodiments, the mass ratio of the chitosan solution, nanocellulose, and emulsifier is 80-85:5-10:5-10;

[0039] Wherein, the concentration of the chitosan solution is 2-3% w / v.

[0040] In some embodiments, the method for preparing the chitosan solution comprises: dissolving chitosan in an acetic acid solution to obtain a 2-3% w / v chitosan solution, wherein the chitosan has a deacetylation degree of 90-95% and a viscosity of 100-200 mPa·s.

[0041] In some embodiments, the emulsifier is fatty alcohol polyoxyethylene ether or glycerol;

[0042] In some embodiments, the nanocellulose is a 5-7% nanocellulose suspension.

[0043] In some embodiments, the coating weight of the secondary primer coating is 4-5 g / m 2 .

[0044] In some embodiments, the mass ratio of hydroxypropyl starch, amylase, acrylate, and water is 12-15:0.01-0.03:15-20:70-85;

[0045] In some embodiments, the acrylate is one or a combination of acrylic acid, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, etc.;

[0046] In some embodiments, the coating weight of the top layer is 4-6 g / m 2 .

[0047] The second aspect of the present invention also provides a method for producing fluorine-free oil-proof paper, comprising:

[0048] Mix coniferous chemical pulp, broadleaf chemical pulp, poplar chemical mechanical pulp, filler, cationic starch, retention aid, brightener and neutral glue evenly to make base paper;

[0049] The pigment, adhesive, water repellent, rheological agent, thickener, defoamer and fungicide are mixed evenly to obtain a first base coating;

[0050] Using the first primer to coat the base paper once;

[0051] The chitosan solution, nanocellulose and emulsifier are mixed evenly to obtain a second primer;

[0052] Using the second primer coating to apply a second primer coating to the paper coated with the first primer;

[0053] Mix hydroxypropyl starch, amylase and water and heat them at 70-75°C for 15-30 minutes, then heat them to 85-90°C for 15-30 minutes, and add acrylate when cooled to 60-70°C and stir for 15-20 minutes to obtain a surface coating;

[0054] The surface coating is used to coat the paper coated with the secondary bottom layer to obtain fluorine-free and oil-proof paper.

[0055] The third aspect of the present invention also provides the use of the above-mentioned fluorine-free oil-proof paper in the fields of food, medicine and cosmetics, especially in the field of food packaging.

[0056] Beneficial Effects of the Invention

[0057] (1) The oil-proof paper of the present invention does not contain fluorine, uses chitosan solution, nanocellulose and emulsifier as the main components of the bottom coating, and uses hydroxypropyl starch, amylase, acrylate and the like as the main components of the surface coating. These components are not only non-toxic and harmless, but also biodegradable and can effectively improve the oil-proof performance of the paper. In addition, by optimizing the base paper preparation process, the prepared paper has excellent physical properties.

[0058] (2) Through the production method of the present invention, the fluorine-free oil-proof paper prepared has reached the standards of high-end products in the market in terms of quantity, whiteness, opacity, smoothness and tensile strength, and the oil-proof grade is higher than grade 9, which can fully meet the needs of various application scenarios. In addition, due to the use of environmentally friendly materials and optimized production processes, the impact of the fluorine-free oil-proof paper of the present invention on the environment during production and use is minimized, which is in line with the current green and environmentally friendly development concept.

[0059] (3) The basis weight of the oil-proof paper of the present invention is 60-65 g / m 2 , whiteness 80-84% ISO, opacity>87%, smoothness 110-120s, transverse tensile strength 2.0-2.1kN / m, longitudinal tensile strength 3.9-4.3kN / m, oil-proof grade ≥ 9. At the same time, the preparation method is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0061] Figure 1 The following are SEM images of the base paper, the comparative example 1 and the paper in Example 1. DETAILED DESCRIPTION

[0062] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0063] It should be noted that, in the present invention, unless otherwise specified, concentrations are all mass concentrations.

[0064] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0065] Embodiment 1:

[0066] Base paper preparation

[0067] The base paper is prepared by uniformly mixing coniferous chemical pulp, broadleaf chemical pulp, poplar chemical mechanical pulp, filler, cationic starch, retention aid, brightener and neutral glue.

[0068] The coniferous chemical pulp has a beating degree of 44°SR and a beating concentration of 4%.

[0069] The broadleaf chemical pulp has a beating degree of 29°SR and a beating concentration of 3.8%.

[0070] The poplar chemical mechanical pulp has a beating degree of 35°SR and a beating concentration of 3.6%.

[0071] The ratio of coniferous chemical pulp, broadleaf chemical pulp and poplar chemical mechanical pulp is 25:50:25.

[0072] The filler is light calcium, nano calcium and diatomaceous earth; the weight ratio of the light calcium, nano calcium and diatomaceous earth is 3:1:1, the filler concentration is 14.5%, and the dosage is 195 kg / ton of paper.

[0073] The concentration of the cationic starch is 2.2%, and the dosage is 10 kg / ton of paper.

[0074] The retention aid is cationic polyacrylamide, with a concentration of 2.3% and a dosage of 0.2 kg / ton of paper.

[0075] The brightener is tetrasulfonic acid, and the dosage is 3kg / ton of paper.

[0076] The neutral glue is AKD, the concentration is 15%, and the dosage is 11kg / ton of paper.

[0077] One-time base coating

[0078] The first bottom coating is controlled to have a coating amount of 5.4 g / m 2 The coating formula is pigment, adhesive, water repellent, rheological agent, thickener, defoamer, bactericide. The formula ratio is calculated as follows:

[0079] Pigment: Adhesive: Water repellent: Rheological agent: Thickener: Defoamer: Bactericide

[0080] =100:10:0.4:0.6:0.4:0.1:0.1 (by mass ratio).

[0081] The pigment is light calcium.

[0082] The adhesive is carboxyl styrene butadiene latex.

[0083] The water repellent is modified glyoxal.

[0084] The rheological agent is methyl methacrylate.

[0085] The thickener is hydroxyethyl cellulose.

[0086] The defoaming agent is cetearyl alcohol;

[0087] The bactericide is organic bromine.

[0088] Secondary base coating

[0089] The first bottom layer coating is blade coating, and the coating amount is controlled to be 4.9g / m 2 The base coating is composed of the following raw materials: chitosan solution, nanocellulose, and emulsifier;

[0090] The chitosan solution is prepared by dissolving chitosan in 1% (V / V) acetic acid solution to obtain a 2% (w / v) chitosan solution. The chitosan has a deacetylation degree of 90% and a viscosity of 100-200 mpa·s.

[0091] The emulsifier is fatty alcohol polyoxyethylene ether.

[0092] The nanocellulose is a 5% nanocellulose suspension.

[0093] The weight ratio of the chitosan solution, nanocellulose and emulsifier is 80:10:10.

[0094] Surface coating

[0095] The surface coating is blade coating, and the coating amount is controlled to be 5.2g / m 2 The surface coating is composed of the following raw materials: hydroxypropyl starch, amylase, acrylate, and water, and the coating temperature is 60°C.

[0096] The acrylic acid ester is butyl methacrylate.

[0097] The weight ratio of the hydroxypropyl starch, amylase, acrylate and water is 12:0.01:15:73.

[0098] The preparation method of the surface coating is to first mix hydroxypropyl starch, amylase and water and heat them at 70°C for 15 minutes, then heat them to 85°C and keep them for 15 minutes, and then add acrylate when cooled to 60°C and stir for 15 minutes to obtain the surface coating.

[0099] Example 2

[0100] Base paper preparation

[0101] The base paper is prepared by uniformly mixing coniferous chemical pulp, broadleaf chemical pulp, poplar chemical mechanical pulp, filler, cationic starch, retention aid, brightener and neutral glue.

[0102] The coniferous chemical pulp has a beating degree of 47°SR and a beating concentration of 4%.

[0103] The broadleaf chemical pulp has a beating degree of 32°SR and a beating concentration of 4.3%.

[0104] The poplar chemical mechanical pulp has a beating degree of 37°SR and a beating concentration of 3.4%.

[0105] The ratio of the coniferous chemical pulp, the broadleaf chemical pulp and the poplar chemical mechanical pulp is 20:60:20.

[0106] The filler is light calcium, nano calcium and diatomaceous earth; the weight ratio of the light calcium, nano calcium and diatomaceous earth is 4:1:1, the filler concentration is 14.7%, and the dosage is 205 kg / ton of paper.

[0107] The concentration of the cationic starch is 2.8%, and the dosage is 10 kg / ton of paper.

[0108] The retention aid is polydimethyldiallylammonium chloride, with a concentration of 2.7% and a dosage of 0.3 kg / ton of paper.

[0109] The brightener is hexasulfonic acid, and the dosage is 3.5 kg / ton of paper.

[0110] The neutral glue is cationic rosin glue with a concentration of 35% and a dosage of 11.8 kg / ton of paper.

[0111] One-time base coating

[0112] The first bottom coating is controlled to have a coating amount of 5 g / m 2 The coating formula is pigment, adhesive, water repellent, rheological agent, thickener, defoamer, bactericide. The formula ratio is calculated as follows:

[0113] Pigment: adhesive: water repellent: rheological agent: thickener: defoamer: bactericide = 100:12:0.6:0.4:0.6:0.2:0.2.

[0114] The pigment is china clay.

[0115] The adhesive is carboxyl styrene butadiene latex.

[0116] The water repellent is polyamide polyurea.

[0117] The rheological agent is methyl methacrylate.

[0118] The thickener is carboxymethyl cellulose.

[0119] The defoamer is polyether modified silicone oil;

[0120] The bactericide is organic bromine.

[0121] Secondary base coating

[0122] The first bottom layer coating is blade coating, and the coating amount is controlled to be 4.8g / m 2 The base coating is composed of the following raw materials: chitosan solution, nanocellulose, and emulsifier;

[0123] The chitosan solution is prepared by dissolving chitosan in 1% (V / V) acetic acid solution to obtain a 3% (w / v) chitosan solution. The chitosan has a deacetylation degree of 95% and a viscosity of 100-200 mpa·s.

[0124] The emulsifier is glycerol.

[0125] The nanocellulose is a 5.8% nanocellulose suspension.

[0126] The weight ratio of the chitosan solution, nanocellulose and emulsifier is 81:9:10.

[0127] Surface coating

[0128] The surface coating is blade coating, and the coating amount is controlled to be 4.6g / m 2 The surface coating is composed of the following raw materials: hydroxypropyl starch, amylase, acrylate, and water, and the coating temperature is 70°C.

[0129] The acrylic acid ester is methyl methacrylate.

[0130] The weight ratio of the hydroxypropyl starch, amylase, acrylate and water is 15:0.03:15:70.

[0131] The preparation method of the surface coating is to first mix hydroxypropyl starch, amylase and water and heat them at 75° C. for 30 minutes, then heat them to 90° C. for 30 minutes, and then add acrylate when cooled to 70° C. and stir for 17 minutes to obtain the surface coating.

[0132] Example 3

[0133] Base paper preparation

[0134] The base paper is prepared by uniformly mixing coniferous chemical pulp, broadleaf chemical pulp, poplar chemical mechanical pulp, filler, cationic starch, retention aid, brightener and neutral glue.

[0135] The coniferous chemical pulp has a beating degree of 46°SR and a beating concentration of 4.1%.

[0136] The broadleaf chemical pulp has a beating degree of 30°SR and a beating concentration of 4.1%.

[0137] The poplar chemical mechanical pulp has a beating degree of 36°SR and a beating concentration of 3.5%.

[0138] The ratio of the coniferous chemical pulp, the broadleaf chemical pulp and the poplar chemical mechanical pulp is 30:50:20.

[0139] The filler is light calcium, nano calcium and diatomaceous earth; the weight ratio of the light calcium, nano calcium and diatomaceous earth is 3.5:1:1, the filler concentration is 15%, and the dosage is 200kg / ton of paper.

[0140] The concentration of the cationic starch is 2.5%, and the dosage is 10.5 kg / ton of paper.

[0141] The retention aid is cationic polyacrylamide, with a concentration of 2.5% and a dosage of 0.25 kg / ton of paper.

[0142] The brightener is hexasulfonic acid, and the dosage is 3.3 kg / ton of paper.

[0143] The neutral glue is AKD, the concentration of AKD is 15%, and the dosage is 13kg / ton of paper.

[0144] One-time base coating

[0145] The first bottom coating is controlled to have a coating amount of 5.4 g / m 2 The coating formula is pigment, adhesive, water repellent, rheological agent, thickener, defoamer, bactericide. The formula ratio is calculated as follows:

[0146] Pigment: adhesive: water repellent: rheological agent: thickener: defoaming agent: bactericide = 100:11:0.5:0.5:0.5:0.15:0.15.

[0147] The pigment is china clay.

[0148] The adhesive is carboxyl styrene butadiene latex.

[0149] The water repellent is ammonium zirconium carbonate.

[0150] The rheological agent is methyl methacrylate.

[0151] The thickener is polyacrylamide.

[0152] The defoamer is polyether.

[0153] The bactericide is organic bromine.

[0154] Secondary base coating

[0155] The secondary bottom layer coating is blade coating, and the coating amount is controlled to be 4.8g / m 2 The base coating is composed of the following raw materials: chitosan solution, nanocellulose, and emulsifier;

[0156] The chitosan solution is prepared by dissolving chitosan in 1% (V / V) acetic acid solution to obtain a 2.5% (w / v) chitosan solution. The chitosan has a deacetylation degree of 95% and a viscosity of 100-200 mpa·s.

[0157] The emulsifier is fatty alcohol polyoxyethylene ether.

[0158] The nanocellulose is a 6% nanocellulose suspension.

[0159] The weight ratio of the chitosan solution, nanocellulose and emulsifier is 85:8:7.

[0160] The surface coating

[0161] The surface coating is blade coating, and the coating amount is controlled to be 5g / m 2 The surface coating is composed of the following raw materials: hydroxypropyl starch, amylase, acrylate, and water, and the coating temperature is 65°C.

[0162] The acrylic acid ester is methyl methacrylate.

[0163] The weight ratio of the hydroxypropyl starch, amylase, acrylate and water is 13:0.01:15:72.

[0164] The preparation method of the surface coating is to first mix hydroxypropyl starch, amylase and water and heat them at 73° C. for 20 minutes, then heat them to 85° C. for 20 minutes, and then add acrylate when cooled to 65° C. and stir for 20 minutes to obtain the surface coating.

[0165] Comparative Example 1:

[0166] The secondary bottom coating in Example 1 was omitted, and the other steps were the same as in Example 1 to obtain paper.

[0167] Comparative Example 2:

[0168] The surface coating in Example 1 was omitted, and the other steps were the same as in Example 1 to obtain paper.

[0169] The paper obtained in the embodiment and the comparative example was subjected to performance tests, and the test results are shown in the following table:

[0170] Table 1 Paper performance test results

[0171]

[0172] It can be seen from Table 1 that the oil-proof grades in Examples 1, 2 and 3 are all over Grade 8, while the oil-proof grades in Comparative Examples 1 and 2 are lower. This is mainly due to the lack of chitosan emulsion coating in the Comparative Example and the lack of starch emulsion coating in Comparative Example 2, resulting in a weaker oil-proof effect.

[0173] The surface morphology of the prepared base paper, the paper in comparative example 1 and example 1 was observed by SEM. Figure 1As shown, it is found that the surface of the base paper presents obvious fibers and fillers, and there are a lot of gaps between the fibers; in Comparative Example 1, the fiber texture can still be seen, but the surface of the paper begins to become smooth, with a certain oil-proof effect; in Example 1, the fibers on the surface of the paper are almost completely covered, the surface becomes smoother, and grease is difficult to penetrate, so it has a better oil-proof grade.

[0174] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A fluorine-free oil-proof paper, characterized in that: include: Base paper, a first bottom layer, a second bottom layer, and a surface layer; the base paper is loaded with the first bottom layer, the second bottom layer, and the surface layer in sequence; The pulp used in the base paper is composed of coniferous chemical pulp, broadleaf chemical pulp, poplar chemical mechanical pulp, filler, cationic starch, retention aid, brightener, and neutral glue; The coating of the first bottom layer is composed of pigment, adhesive, water repellent, rheological agent, thickener, defoamer and bactericide; The coating of the second bottom layer is composed of chitosan solution, nanocellulose and emulsifier; The coating of the surface layer is composed of hydroxypropyl starch, amylase, acrylate and water; The mass ratio of the chitosan solution, nanocellulose and emulsifier is 80-85:5-10:5-10; wherein the concentration of the chitosan solution is 2-3% w / v; The preparation method of the chitosan solution is as follows: dissolving chitosan in an acetic acid solution to obtain a 2-3% w / v chitosan solution, wherein the chitosan has a deacetylation degree of 90-95% and a viscosity of 100-200 mpa·s; The mass ratio of the hydroxypropyl starch, amylase, acrylate and water is 12-15:0.01-0.03:15-20:70-85; the acrylate is one or a combination of acrylic acid, butyl acrylate, methyl methacrylate, ethyl methacrylate and butyl methacrylate; The preparation method of the surface layer is as follows: hydroxypropyl starch, amylase and water are mixed and heated at a temperature of 70-75° C. for 15-30 minutes, then the temperature is raised to 85-90° C. for 15-30 minutes, and the acrylate is added and stirred for 15-20 minutes when the temperature is cooled to 60-70° C. to obtain the surface layer coating; The emulsifier is fatty alcohol polyoxyethylene ether or glycerol; Or, the nanocellulose is a 5-7% nanocellulose suspension; Or, the coating amount of the secondary bottom coating is 4-5g / m 2 .

2. The fluorine-free oil-proof paper according to claim 1, characterized in that: The mass ratio of the coniferous chemical pulp, the broadleaf chemical pulp, and the poplar chemical mechanical pulp is 20-30:50-60:20-30; Or, the amount of filler is 190-210kg / ton of paper; Or, the cationic starch is used in an amount of 10-11 kg / ton of paper; Or, the amount of the brightener is 3-3.5 kg / ton of paper; Or, the amount of the retention agent is 0.2-0.3 kg / ton of paper; Or, the usage of the neutral glue is 10-15kg / ton of paper.

3. The fluorine-free oil-proof paper according to claim 1, characterized in that: The coniferous chemical pulp has a beating degree of 43-47°SR and a beating concentration of 3.9-4.2%; Or, the broadleaf chemical pulp has a beating degree of 28-32°SR and a beating concentration of 3.8-4.3%; Or, the poplar chemical mechanical pulp has a beating degree of 35-37°SR and a beating concentration of 3.4-3.6%; Or, the filler is light calcium, nano calcium and diatomaceous earth; the weight ratio of the light calcium, nano calcium and diatomaceous earth is 3-4:1:1, and the filler concentration is 14-16%; Or, the concentration of the cationic starch is 2-3%; Or, the retention aid is cationic polyacrylamide or polyethyleneimine or polydimethyldiallylammonium chloride, and the concentration is 2.3-2.7%; Or, the brightener is tetrasulfonic acid or hexasulfonic acid; Or, the neutral glue is AKD or cationic rosin glue, the concentration of AKD is 15%, and the concentration of cationic rosin glue is 35%.

4. The fluorine-free oil-proof paper according to claim 1, characterized in that: The mass ratio of the pigment: adhesive: water repellent: rheological agent: thickener: defoamer: bactericide is 100:10-12:0.4-0.6:0.4-0.6:0.4-0.6:0.1-0.2:0.1-0.

2.

5. The fluorine-free oil-proof paper according to claim 1, characterized in that: The pigment is light calcium or porcelain clay; Or, the adhesive is carboxylated styrene-butadiene latex or acrylic emulsion; Or, the water repellent is potassium zirconium carbonate, modified glyoxal, polyamide polyurea or ammonium zirconium carbonate; Or, the rheological agent is modified acrylic acid; Or, the thickener is polyurethane emulsion, carboxymethyl cellulose, hydroxyethyl cellulose, polyvinyl alcohol or polyacrylamide; Or, the defoamer is polyether, C18-C20 higher fatty alcohol or silicone; Or, the bactericide is an organic bromine; Or, the coating amount of the base coating is 4-6g / m 2 .

6. The fluorine-free oil-proof paper according to claim 1, characterized in that: The coating amount of the surface coating is 4-6g / m 2 .

7. A method for producing fluorine-free oil-proof paper according to any one of claims 1 to 6, characterized in that: include: Mix coniferous chemical pulp, broadleaf chemical pulp, poplar chemical mechanical pulp, filler, cationic starch, retention aid, brightener and neutral glue evenly to make base paper; The pigment, adhesive, water repellent, rheological agent, thickener, defoamer and fungicide are mixed evenly to obtain a first base coating; Using the first primer to coat the base paper once; The chitosan solution, nanocellulose and emulsifier are mixed evenly to obtain a second primer; Using the second primer coating to apply a second primer coating to the paper coated with the first primer; The surface coating is used to coat the paper coated with the secondary bottom layer to obtain fluorine-free and oil-proof paper.

8. Use of the fluorine-free oil-proof paper according to any one of claims 1 to 6 in the fields of food, medicine and cosmetics.

Citation Information

Patent Citations

  • Preparation method of degradable antibacterial chitosan modified nano cellulose oil-proof paper

    CN116623459A

  • Multilayer coating for paper based substrate

    US20110206914A1

  • Method of modifying polymer barrier films

    US20220205184A1